Immune checkpoint-induced arthritis: a comprehensive single-cohort descriptive analysis from clinical evaluation to histology - Meric de Bellefon, Laurent; Natalucci, Francesco; Nzeusseu Toukap, Adrien; Sokolova, Tatiana; Galant, Christine; Aboubakar, Frank; Baurain, Jean-François; Cornélis, Frank; Borbath, Ivan; Durez, Patrick (Frontiers in Medicine, 2025)
Background/purposeImmune checkpoint inhibitor-induced arthritis (ICI-IA) is the most common rheumatic immune-related adverse event (irAEs). Its pathogenesis remains unknown. Ultrasound (US)-guided synovial biopsy (USGSB) has been proven to be a safe and reliable procedure in rheumatoid arthritis (RA), enlarging the understanding of synovitis in RA. To the best of our knowledge, no studies have analyzed the histology of ICI-induced arthritis. This study aimed to describe ICI-IA from clinical presentation to histology.Materials and methodsPatients who developed inflammatory arthritis while under treatment by ICIs were enrolled. A US assessment of 38 joints [shoulders, elbows, knees, wrists, metacarpophalangeal joints (MCPs), proximal interphalangeal joints (PIPs), and metatarsophalangeal joints (MTPs)] was systematically performed for inflammatory assessment and joint selection before synovial biopsy. Histopathological analyses consisted of semiquantitative scores for histological parameters (synovial hyperplasia, fibrinoid necrosis, hypervascularization, and inflammatory infiltrate) and immunohistochemistry staining (CD3, CD20, CD138, and CD68). As a control group, we enrolled age- and sex-matched untreated early RA (ERA) patients with synovial tissue available.ResultsA total of 13 patients were included [men/women (10/3), with a median age of 65 years (interquartile range: IQR: 14.5)]. Overall, seven patients suffered from polyarthritis (53.8%), and five (38.4%) suffered from oligoarthritis. The US pre-biopsy evaluation detected synovitis in 23.4% of joints; the most involved was the knee, followed by wrist, elbow, MCP2, MCP3, and MTP 2–5. Samples for synovial tissue analysis were primarily obtained from the knee (69.2%). The histology of ICI-induced arthritis demonstrated a synovial inflammation similar to that found in ERA. ICI-IA and ERA show similar clinical and histological characteristics.ConclusionClinically, ICI-IA manifested as oligoarthritis and polyarthritis, similar to RA. Synovial histology in ICI-induced arthritis is indistinguishable from RA, suggesting common pathogenic mechanisms. Further transcriptomics analyses are ongoing to better describe this new arthritis condition.